Sunatan Gratis Bagi Masyarakat Toddopuli bersama Medika Farma - Jaya, Rachmat; Pannyiwi, Rahmat; Nurhaedah, Nurhaedah; Zaenal, Zaenal; Aripa, Lusyana; Wahyuni, Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The Indonesian Pediatrician Association also states that Sunnat (circumcision) can prevent the buildup of dirt and prevent phimosis, both of which can cause infections in the genitals of babies and children. However, sometimes the implementation of this Sunnat (circumcision) cannot be carried out because of significant cost factors, so the implementation is delayed. One effort so that every child can perform Sunnat (circumcision) is by carrying out mass circumcision activities in the community around the Medika Farma Clinic. From this mass circumcision activity, it is hoped that many children in Indonesia will be circumcised, thereby achieving an increase in the health status and good growth of Indonesian children.